Last Words of Abubakar Shekau: A Testament in the Politics of Jihadi Extraversion - (:unkn) unknown (My University, 2021)
The last audio put out by Nigerian jihadi leader Abubakar Shekau before his death is a rare source, distinct from his usual public propaganda. Addressed to internal jihadi audiences, it sheds light on a number of key aspects, from the events that led to his death to the political economy of plunder, a key issue in Shekau’s jihad. Its most interesting takeaway, however, is about the relation between a local jihadi organisation and the global jihadi structures of Al-Qaeda and the Islamic State. It illustrates Shekau’s complex and ultimately unsuccessful strategies of extraversion—using the appeal and resources of global jihad while trying to contain its demands.
Keywords: African Research